(3dZR dHgGA GdOjf GdSHci aj Gdfjds - (3CMeO Hf Ydj Hf YHO GdcGaj GdSHcj , CHh MGeO, HgGA GdOjf, J (B763 (3g` s
(3ChdgG (B:s
(3CdGdjJ TYQi gd CHjJfi djdg HhGO hMhdi UGMH hNdj s
(3BNQgG (B:s
(3ef Jdi ajge Jbd dGbjJ SjOge eKd GdJiJSQi HgG GdSGQi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3HgG fXGe GdJYbjHIs
(3cJHg dUdGM GdOjf GdUaOiGOHs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs